Cu-Catalyzed Selective Oxygenation of Aryl C–H Bonds with O2 and MnO2 as Terminal Oxidants - Ahmad, Muhammad Siddique; Wang, Qifeng; Meguellati, Kamel (Synlett, 2025)
Herein, we present efficient methods for the selective copper-catalyzed oxidation of aromatic C–H bonds in the presence of O2 and/or MnO2. Various 2-arylpyridines and 2-arylpyrimidines are used for the controlled synthesis of mono- and diacetoxylative products in moderate to good yields (29–99%) in the presence of CuO(nano) (20 mol%), O2 and HOAc/Ac2O as an acetoxy source and solvent. The mono selective hydroxylation of C–H bonds is also achieved with Cu(OAc)2 as the catalyst. Mechanistically, a trivalent copper intermediate might be involved in the catalytic cycle.
Keywords: copper; C–H bond activation; hydroxylation; acetoxylation; 2-arylpyridines